Association between plasma vitamin B5 and coronary heart disease: Results from a case-control study - Sun, Pengfei; Weng, Haoyu; Fan, Fangfang; Zhang, Nan; Liu, Zhihao; Chen, Ping; Jia, Jia; Zheng, Bo; Yi, Tieci; Li, Yuxi; Zhang, Yan; Li, Jianping (Frontiers in Cardiovascular Medicine, 2022)
Aim: The relationship of vitamin B5 and coronary heart disease (CHD) is still uncertain. This case–control study was performed to evaluate the relationship between the plasma vitamin B5 concentration and the risk of CHD. Methods: The study involved 429 patients with >70% stenosis of the coronary arteries on coronary angiography and 429 matched controls were included for age ± 2 years, gender, and date of coronary angiography examination ± 180 days. Logistic regression analyses were performed to evaluate the association between plasma vitamin B5 and the risk of CHD. Results: An L-shaped relationship was found between the plasma vitamin B5 concentration and CHD. Compared with patients with low vitamin B5 (first quartile, <27.6 ng/ml), the odds ratio (OR) and 95% confidence interval (CI) for participants in the third quartile (34.9–44.0 ng/ml) and fourth quartile (≥44.0 ng/ml) were 0.42 (95% CI, 0.26–0.70) and 0.49 (95% CI, 0.29–0.82), respectively. In the threshold effect analysis, the risk of CHD significantly decreased as the vitamin B5 concentration increased (per 10-ng/ml increment: OR, 0.71; 95% CI, 0.57–0.89) in participants with a plasma vitamin B5 concentration of <40.95 ng/ml; however, an increased plasma vitamin B5 concentration was no longer associated with a decreased risk of CHD (per 10-ng/ml increment: OR, 1.00; 95% CI, 0.87–1.14) in participants with a plasma vitamin B5 concentration of ≥40.95 ng/ml. The association between vitamin B5 and CHD was stronger in ever or current smokers than non-smokers (p-interaction = 0.046). Conclusion: Plasma vitamin B5 has an L-shaped relationship with CHD, with a threshold around 40.95 ng/ml. This association was modified by smoking.